Ecological values, narcissism, and materialism: a comparison of business students in the USA and the Netherlands. (2014) - Westerman, James W.; Beek, Erik van; Westerman, Jennifer; Whitaker, Brian G.
As business has a large impact on the natural environment, it is important to study the environmental values of business school students. This research focuses on the personality trait of narcissism, and its impact on materialism and environmental values. Data were collected in an exploratory analysis of the relationships between narcissism, materialism, and environmental values from business students in the USA and the Netherlands. Results indicate that business student narcissism was significantly associated with higher levels of materialism, and higher levels of materialism were associated with lower environmental values in both the USA and the Netherlands. As business students represent a critical element in creating and developing a more sustainable economic model, these results point to a pressing need for higher education to engage in more aggressive interventions to educate and produce future business leaders with a greater concern for environmental stewardship.